Regional Autonomy In Health Perspective Law 23 Year 2014 - Cintya Noer (Socio Legal and Islamic Law, 2022)
Good governance in the era of globalization, provides the best service to requests from the community. The implementation of the government actually experienced difficulties in handling  the COVID-19 outbreak that has spread all over the world. Determination of Lockdown or semi-lockdown that  carried out by the Regional Government due to the increasing spread of the Covid-19 disease  increasing case significance. Even as of April 3, 2020, positive cases of Covid 19 have reached 1,986. The method in this study is the result of the Literature Review, where the focus is on  This research method is the result of understanding and developing from the study of the existing literature  been there before. This research method is based on reviewing or reviewing critically  knowledge, ideas contained in the body of written literature as well as formulating theoretical contributions and  certain methodological topics. The basic wisdom of the word wise means clever, shrewd, capable, and expert. As for  difference between policy and discretion. Health is defined as a basis for understanding  health policy, especially in the health sector. problems in the health sector,  if a condition has caused dissatisfaction with the majority of the community.  This means that the problems that occur are increasing in dominant values and needs.  regional autonomy policy based on Law 23 of 2014 in the field of Health the basic policy of the word  wise means clever, clever, capable, and expert. Policy is related to one's ability  while wisdom is related to a decision to allow it about prohibition  which have been made for certain reasons. In society this is a form of  response to complaints against local governments regarding ongoing problems.Keywords: good governance, health, regional autonomy